RETRACTED: Quantitative analysis and visualization of literature on acupuncture and related TCM therapies for the treatment of colorectal cancer based on CiteSpace - Li, Zeli; Xiong, Qianwen; Li, Shuwen; Chen, Wenxiang; Xu, Nenggui; Qiu, Fanghua (Frontiers in Oncology, 2024)
We analyzed the literature describing the results of treatment of colorectal cancer (CRC) using acupuncture in the past three decades from the Web of Science (WoS) and Chinese databases (including CNKI, WANGFANG and VIP), and summarized the current development of CRC treatment as well as future research directions through the presentation of maps and visualization analysis. Methods: We searched the WoS and Chinese databases. Relevant articles were exported, and the data were organized using Excel software and was visualized and analyzed using CiteSpace software. Results: A total of 355 articles from the WoS and 95 articles from Chinese databases were selected for inclusion in the analysis. The articles in WoS were sourced from 174 journals, 1274 institutions, and 66 countries, and covered 299 keywords. The articles in the Chinese databases were sourced from 43 journals, 111 institutions, and 3 countries, and included 126 keywords. The article with the most citations in the WoS was cited 128 times and in the Chinese databases, the article with the most citations was cited 120 times. Acupuncture, CRC, rectal cancer, apoptosis, warm acupuncture, traditional Chinese medicine (TCM) and gastrointestinal function were mentioned most frequently in the WoS. CRC, electroacupuncture, gastrointestinal function, rectal cancer, acupuncture and moxibustion, acupuncture, and colon cancer were mentioned most frequently in the Chinese databases. Conclusion: Both the WoS and Chinese databases showed a gradual increase in the number of articles related to acupuncture treatment for CRC, indicating a growing interest in this area. Acupuncture treatments are diverse, including warm acupuncture, auricular acupuncture, acupuncture injection, and electroacupuncture. They are often used in combination with drugs to treat symptoms such as depression, nausea and vomiting, pain, diarrhea, and urinary and fecal incontinence, which are commonly associated with CRC.